Rajids ovipositing on marine litter: a potential threat to their survival - Espinoza Morriberón, Dante (2023)
Marine litter is a complex environmental issue threatening the well-being of multiple organisms. In the present study, we present an overlooked pathway by which marine litter interaction with certain ovigerous skates (Family: Rajidae) communities could compromise their survival. We propose that skates from the genus Sympterygia deposit their egg capsules on marine litter substrates by accident, which are then washed ashore still unhatched. We conducted 10 monitoring surveys on three beaches of La Libertad Region, on the north coast of Peru, looking for marine litter conglomerates to determine the presence of egg capsules. We registered a total of 75 marine litter conglomerates, containing 1595 egg capsules, out of which only 15.9 % were presumably hatched, and 15.8 % were still fresh. Fishing materials were identified as the main item in marine litter conglomerates. We conclude that this behavior could contribute to the decline of Sympterygia communities, although further research is needed.